We have to solve log(15) [1/(3^x + x - 5)] = x * (log(15) 5 - 1).

log(15) [1/(3^x + x - 5)] = x * (log(15) 5 - 1)

=> log(15) [1/(3^x + x - 5)] = x*log(15) 5 - x

=> log(15) [1/(3^x + x - 5)] =...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

We have to solve log(15) [1/(3^x + x - 5)] = x * (log(15) 5 - 1).

log(15) [1/(3^x + x - 5)] = x * (log(15) 5 - 1)

=> log(15) [1/(3^x + x - 5)] = x*log(15) 5 - x

=> log(15) [1/(3^x + x - 5)] = x*log(15) 5 - log (15) 15^x

=> log(15) [1/(3^x + x - 5)] = log(15) (5^x/ 15^x)

=> [1/(3^x + x - 5)] = 5^x/ 15^x

=> [1/(3^x + x - 5)] = 1/ 3^x

=> 3^x = 3^x + x - 5

=> x - 5 = 0

=> x = 5

**We get x = 5**